Inactivation of Factor VIII by a Mechanism Independent of the Generation of Thrombin - Triantaphyllopoulos, D C (Thrombosis and Haemostasis, 1979)
Thrombin first activates and then inactivates factor VIII and for this reason thrombin has been considered responsible for the inactivation of factor VIII which occurs during clotting. Experiments described in this paper indicated that the activity of factor VIII is not reduced in factor IX or factor X deficient sera, while on the other hand this factor becomes inactivated in blood anticoagulated with high concentrations of hirudin which inhibit thrombin activity completely. This suggests that some other factor, besides thrombin, which is generated only in trace amounts in factor IX or factor X deficient plasmas, is also able to inactivate factor VIII. Purified factor X activated with insolubilized trypsin was added to purified preparations of factor VIII, which were free of both fibrinogen and prothrombin. Factor Xa was allowed to act for 5-60 minutes and then inactivated with phenylmethanesul- fonyl fluoride. Depending on the duration of the action of factor X a partial or complete inactivation of factor VIII was observed. This inactivation was also observed in the presence of hirudin, thus excluding the possibility that the effect was due to contamination with trace amounts of thrombin.